The Historical Typology of Sacred Music of the Christian Tradition - Zosim, Olga (Journal of History Culture and Art Research, 2019)
Three stages can be distinguished in the history of Christian music – the early Christian, medieval and modern, each of which, with a plurality of styles, genres and forms, has internal integrity and unity. The integrity of each historical type of sacred music is based on a common understanding of the sacred as a key category of religious art. The sacred in the early Christian liturgy appears as a unity of text, music and rite in the sacrament of the Eucharist as the pinnacle of religious communication, while music aimed at conveying religious emotions was not considered an autonomous, and therefore an aesthetic object. In the medieval liturgy, the sacrament of the Eucharist as the pinnacle of religious communication is inextricably linked with aesthetic categories: solemnity, prayerfulness, concentration of liturgical music, the exaltation of liturgical texts using exclusively archaic languages, become the main markers of the sacred. In Modern Period, Protestant theology rethinks the doctrine of church sacraments, which is reflected in the liturgical practice of other Christian denominations. As a result, the syncretic unity of text, music and ritual is lost in the sacred art of the Modern Period, which leads to a transformation of the relationship between its aesthetic and sacred components. This contributed to the formation of a multiplicity of forms of liturgical music in various Christian denominations, where the verbal (Protestant tradition) or the musical-aesthetic (Catholic and Orthodox traditions) component could be priorities. The autonomization of music in worship led to the emergence of non-liturgical, quasi-sacred music, which at a new historical stage actualizes medieval genres and forms, as well as meditation as the basis of musical dramaturgy, while refusing the key category of religious art – religious communication. The characterization of the historical stages of development of Christian music will allow the reader to understand both the internal mechanisms of its external transformation in the process of evolution, and to understand the reason for the diversity of its modern forms, including the appearance of those that have lost their direct connection with worship.